(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Labor laws determine the cases of termination of the work association. These legislations guarantee a retirement salary to the worker whose service is terminated, provided that he is protected and covered by social security, meaning that he fulfills the legal requirements, which include the payment of pension contributions. However, there are exceptional cases in which they expire. The work relationship, whether in collective or individual labor contracts, without those contracts fulfilling the legal requirements, whether in terms of years of service, Or in terms of collecting pension contributions during the period of his service or work with the employer, especially if he is not protected or covered by social security, in this case the person is entitled to a reward known as the end-of-service gratuity , as it has been approved to protect and compensate him and his family for his loss of work and the possibility of He will have not obtaining another job opportunity after the end of his service, especially if he is old, so we will try to explain the issue from various aspects in accordance with the Iraqi legislation in force.